2020
DOI: 10.2147/dddt.s242493
|View full text |Cite
|
Sign up to set email alerts
|

<p>Oxymatrine Liposomes for Intervertebral Disc Treatment: Formulation, in vitro and vivo Assessments</p>

Abstract: Intervertebral disc degeneration (IVDD) is the main cause of modern low back pain, leading to high societal economic costs. To find an effective medical treatment for this disease, oxymatrine liposomes (OMT-LIP) were prepared with the pH-gradient method. Materials and Methods: Nucleus pulposus (NP) cells from Sprague-Dawley rats were used for the cell experiments. Kunming mice were used for in vivo imaging. LIP were employed to deliver OMT, and the particle size, ζ-potential, morphology, in vitro stability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…On the one hand, appropriate intensity of ultrasound stimulation can promote cell growth and functional recovery, on the other hand, the effect of ultrasonic force makes it easy to fuse between microbubbles and cells. [32][33][34][35]…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, appropriate intensity of ultrasound stimulation can promote cell growth and functional recovery, on the other hand, the effect of ultrasonic force makes it easy to fuse between microbubbles and cells. [32][33][34][35]…”
Section: Discussionmentioning
confidence: 99%
“…Liposomes are biocompatible nanocarriers used to deliver various drugs. Wang et al [ 132 ] found that such delivery enhanced drug distributions in targeted areas. Oxymatrine-liposomes enhanced drug accumulation in intervertebral discs, while reducing NP cell apoptosis and ECM degeneration.…”
Section: Natural Pharmacological Productsmentioning
confidence: 99%
“…Nanoparticles have large surface areas and pore volumes, which allow them to effectively load drugs [ 157 ]. A combination of a nanomaterial and oxymatrine increased drug anti-IDD activity, suggesting a novel route of drug administration [ 132 ]. Natural products are prime sources of drug development [ 158 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Lipid nanostructures are the most investigated carriers for targeted drug delivery [ 39 , 86 , 87 , 88 ]. Among them, liposomes are artificially prepared vesicles made of phospholipid bilayers [ 86 , 89 ] having the potential for the treatment of arthritic diseases [ 90 , 91 , 92 , 93 ]. The liposomal encapsulation of natural compounds or drugs was proposed by several researchers and many data in the field demonstrated the improvement of their performances [ 6 , 94 ].…”
Section: Recent Advances In Liposomes Technologymentioning
confidence: 99%